A Database Interface System for the Preop Expert System - Pharasi, Mathabo (My University, 1991)
PREOP is a medical expert system which is being developed on the expert-system shell NEXPERT. PREOP determines the risk of cardiac complications for a patient about to undergo noncardiac surgery, and recommends a programme of medication intake for the patient. PREOP's final database and hardware requirements are uncertain, and so are its final functionalities. These uncertainties necessitate a database interface which facilitates overall system flexibility, maintainability, modularity, and integration with existing information systems. These objectives are best achieved by a loosely coupled database interface which is not under NEXPERT's control. PREOP-DIS is a loosely coupled database interface system for PREOP. This project uses the relational model to design PREOP' s database and implements the database on the relational DBMS SYBASE. The project implements PREOP-DIS as a C program that communicates data between PREOP and the SYBASE database by dynamically making calls to NEXPERT and to the SYBASE dataserver.
Keywords: PREOP-DIS; PREOP expert; database interface